If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7m+5=3(m+2)
We move all terms to the left:
7m+5-(3(m+2))=0
We calculate terms in parentheses: -(3(m+2)), so:We get rid of parentheses
3(m+2)
We multiply parentheses
3m+6
Back to the equation:
-(3m+6)
7m-3m-6+5=0
We add all the numbers together, and all the variables
4m-1=0
We move all terms containing m to the left, all other terms to the right
4m=1
m=1/4
m=1/4
| 25+8x/16-11=16 | | 1/2x=288 | | 28-7x(9/9)=21 | | 7-(6g/9)=10 | | 3×(6+5k)=18+5k | | 3(x+7)=-(5-x)+6 | | 3-2x=4x+7 | | 3k+1=12k+2 | | 11=23+-4x | | w=1.214+6 | | (7x*x)-18x+27=0 | | 9u=18 | | 30-(x/20)=x/80 | | 30-(x/20)=3x/80 | | 30-(x/40)=3x/80 | | 30-(2x/40)=x/80 | | 5y-2(4y-5)=11 | | 30-(x/40)=x/40 | | x/40=30-(x/40) | | 18/(p+6)=2 | | 0.4y+7=0.16(5y-2) | | 16-4f=32 | | 4(x-3)=3(x-1) | | x+2/6=2x+7/4 | | 5z+3=z-7 | | 8-x/3=2x-3/5 | | 4(3.2x+5)=4.2 | | 8-x/3=2x- | | 7x/3x-1=2 | | 10x+3x=194.88 | | x+10+3x+10=76 | | 12x+14(50-x)=660 |